Habitação de interesse social em tempos de pandemia: necessidade de flexibilidade nas unidades habitacionais do Programa Minha Casa Minha Vida em Concórdia no Estado de Santa Catarina - Fontana, Fabiana Carla Vargas de Andrade (Universidade do Vale do Rio dos Sinos, 2021)
This dissertation is focused on social housing and on the questioning of the processes currently used in Brazil, regarding architectural adaptability and flexibility. The research sought to verify whether the adoption of evolutionary architectural design could contribute to the adequacy of the dwellings to the users' need for distance and/or social isolation and to answer the following questions: can the production of social interest housing collaborate to the new demands caused by COVID-19? Can the application of flexibility concepts together with the norms prescribed by NBR 15.575/2013 indicate a new path to be followed by housing programs? In order to answer these questions, the general objective was to identify the possibility of inserting the concepts of flexibility in addition to the norms prescribed by NBR 15.575/2013 for new houses destined for housing programs so that they are able to cope with the demands caused by COVID-19. The research falls within the Post Occupancy Evaluation method of the Minha Casa Minha Vida Program in the housing developments of the Frei Lency II and Nova Brasília II neighborhoods in the municipality of Concordia/SC. In this research qualitative aspects were analyzed, and the main focus was to evaluate the functional, behavioral and environmental issues, in order to subsidize future improvements in the field of quality in the construction of new HIS. Considering the current pandemic context, many families have spent more time at home, and school has become part of the homes, where people have adopted safety measures that include social isolation. Routines within the home have changed due to the increase of family members at home at the same time or due to the increase of activities to be carried out in the same period of time. In the case of infected family members, isolation within the same residence, shared with healthy residents, has become necessary, as they are often elderly people who are more vulnerable to infection by COVID-19. According to the bibliographies studied, the housing production is marked by decades of absence of essential elements related to spatial quality and urban insertion, and it can be noticed that both in the Frei Lency II and Nova Brasília II neighborhoods, the houses present repeated implantations, standardization of the units, peripheral implantations, absence of regionality and cultural issues, which are recurrent problems of the housing production of PMCMV. In both cases studied it was possible to notice that most of the modifications occurred in the kitchen because it did not have a wood stove, essential furniture for the region's inhabitants, both for heating and cooking food. In this way, it is considered fundamental to develop the project with the use of architectural flexibility concepts, since this criterion must be supported by technical follow-up. Another important point is to allow the dweller to participate in the design process, and thus, to make a reading of each family profile, as well as to enable the establishment of qualitative guidelines for future constructions.
Keywords: Flexibilidade; Adaptabilidade; Habitação; Moradia; Programa Minha Casa Minha Vida; Flexibility; Adaptability; Dwelling; Housing; My Home My Life Program; ACCNPQ::Ciências Sociais Aplicadas::Arquitetura e Urbanismo